The Effectiveness of Facilitator’s Role in Sustainable Farmer Community Empowerment - Fibrianingtyas, Alia; Pertiwi, Vi'in Ayu; Rayesa, Neza Fadia (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
The smart city concept imposed by the Batu City Government of East Java Province was adopted from the 4.0 industrial revolution, but in reality, it has not been successful. The majority of the farmers are over 50 years old, so they have difficulty accepting this innovation. To address these gaps, it is necessary to play the role of community development actors (instructors, facilitators, or empowerers) to create a balance in the socio-ecosystem. Therefore, this study aims to analyze the effectiveness of the role of farmer assistant staff (TPP) to support agricultural extension to realize Batu smart city. The research was conducted in Batu City, especially Bumiaji, Junrejo, and Batu sub-districts. This study uses a quantitative approach with descriptive statistical data analysis. Data were obtained through interviews using questionnaires to farmers who received direct counseling and assistance from farmer assistants, especially in accessing Among Tani facilities. The respondent determination technique used in this study is saturated sampling. The samples selected were all Farmer Assistance Workers (TPP) in Batu City, totaling 40 people, 17 people from Bumiaji District, 13 people from Junrejo District, and ten people from Batu District. The results showed that the average age of the assistants was young and had a minimum education of S1 so that they were able to facilitate farmers, especially in accessing technology. The role of farmer assistants is very effective as facilitators, environmental analyzers, motivators, and farmer assistants, even though they are only included in the practical category as marketing partners. The effectiveness of farmer empowerment shows that from meeting the information needs needed by farmers, the level of cooperation between farmers and the level of innovation adaptation in the farmer's environment is high